INCREASING RELIGIOUS AWARENESS THROUGH LEARNING THE FIQH OF ABLUTION AND PRAYER: A CASE STUDY OF CHILDREN IN BABO VILLAGE - Muhammad Rizki Pratama; Siti Khadijah Anwar (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2024)
This study aims to enhance children's religious awareness through the teaching of fiqh (Islamic jurisprudence) on ablution (ablution) and prayer in Desa Baru, Aceh Tamiang Regency. The main issue addressed is the low level of understanding among children regarding the correct procedures of ablution and prayer, which impacts the quality of their daily worship. This research employs a qualitative approach with a case study method. Data was collected through direct observation, in-depth interviews, and documentation during the educational program implemented within the KKN activities. The research findings indicate a significant improvement in children's understanding and practice of worship after participating in the fiqh ablution and prayer learning program. Children who previously had limited knowledge of essential aspects of ablution and prayer became more disciplined in performing their religious duties. Additionally, there was an increase in their motivation to learn more about religion, and positive behavioral changes were observed, particularly in maintaining cleanliness before prayer and punctuality in performing prayers. In conclusion, this fiqh learning program had a positive impact on enhancing children's religious awareness in Desa Baru